Chalcone analogues: Synthesis, activity against Meloidogyne incognita, and in silico interaction with cytochrome P450. Issue 4 (3rd February 2019) - Silva, Fabíola J.; Campos, Vicente P.; Oliveira, Denilson F.; Gomes, Vanessa A.; Barros, Aline F.; Din, Zia Ud; Rodrigues‐Filho, Edson
Abstract: To contribute the development of new products to control plant‐parasitic nematodes, 12 chalcone analogues were synthesized and screened for activity against Meloidogyne incognita. Three caused mortality greater than negative controls in second‐stage juvenile M. incognita, with values varying from 19.9% to 100%. The most active chalcone analogue was (1 E, 4 E )‐1, 5‐di(4‐nitrophenyl)‐2‐butylpenta‐1, 4‐dien‐3‐one (compound6 ), which had an LC50 value of 41 µg/ml. Under the same conditions, the commercial nematicide Carbofuran ® (2, 2‐dimethyl‐2, 3‐dihydro‐1‐benzofuran‐7‐yl methylcarbamate) presented an LC50 equal to 101 µg/ml. When this chalcone analogue was applied to tomato plants infested with M. incognita, reductions in the numbers of galls and eggs of 51% and 68% were observed, respectively. According to in silico studies, the enzyme target of compound6 in M. incongita is cytochrome P450, which is important for the oxidation of several substances in the nematode. Therefore, compound6 is potentially useful for the development of new products to control M. incongita .